The Influence of Halal Brand Awareness and Religiosity on Muslim Consumers' Halal Product Purchasing Decisions - Muhammad Reza; Anton Agus Setyawan (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2026)
This research investigates the influence of halal brand recognition and religious commitment on Muslim consumers’ purchasing decisions regarding halal products. Utilizing a quantitative research framework, original data were obtained through questionnaires from 150 purposively selected respondents who were Muslim, aged 21 or older, and had purchased halal products. Three constructs were assessed using a five-point Likert scale: Consumer Awareness of Halal Brands, Religious Commitment, and Halal Product Purchase Decisions. Halal Brand Awareness assesses consumers’ knowledge and recognition of halal-certified products, including awareness of ingredients, labeling, and compliance with Islamic dietary laws. Religiosity examines the impact of personal religious beliefs and practices on consumer behavior. Halal Purchase Decision reflects consumers’ evaluation and commitment to acquiring halal products, considering factors such as religious guidance, hygiene, quality, family influence, and health. The analysis of the data indicated that halal brand awareness and religiosity both positively and significantly influence Muslim consumers’ decisions to purchase halal products, confirming the study’s hypotheses. These findings provide insights for marketers to enhance consumer education and emphasizing the significance of halal certification, while also underscoring the role of religiosity in shaping purchasing behavior.